Determining the Efficiency of Photoelectrode Materials by Coupling Cavity‐Microelectrode Tips and Scanning Electrochemical Microscopy. Issue 11 (2nd June 2020) - Visibile, Alberto; Baran, Tomasz; Rondinini, Sandra; Minguzzi, Alessandro; Vertova, Alberto
Abstract: Photoelectrochemical water splitting (PEC‐WS) is a promising route to obtain hydrogen (and oxygen) from sunlight and water. However, too many semiconductors show poor stability, due to photodegradation phenomena in aqueous solutions, thus loosing efficiency under operative conditions. Aim of this paper is to introduce a simple and fast method for screening different semiconductor materials and identify their efficiency in H2 (or O2 ) production with respect to photocorrosion. This method could be used with any finely dispersed semiconductor (powder) for a fast, preliminary evaluation of the material's behaviour without interferences from the supporting material (i. e. FTO) or any binder. The method is based on the combination of scanning electrochemical microscopy (SECM) in the tip generation/substrate collection (TG/SC) mode and of cavity microelectrodes as SECM tips. Here, we show results obtained on three powder materials, namely core‐shell CuI/CuO, CuI and TiO2 . Abstract : A closer look : A novel method to evaluate the photoefficiency of hydrogen (or oxygen) production on powder materials for photoelectrochemical water splitting is proposed. Scanning electrochemical microscopy used in tip‐generation/substrate‐collection mode allows to discriminate between the desired electron transfer and recombination and/or undesired side reaction that may lead to material photodegradation.